Efektivitas Media Pembelajaran Berbasis Adobe Express dalam Meningkatkan Pemahaman Konsep pada Mata Pelajaran Informatika SMPN 2 Sindangagung - Malasari, Mala Nur; Lutfi, Ahmad Fajir (Indo-MathEdu Intellectuals Journal, 2025)
Teaching and learning activities in the Informatics subject, particularly at the lower grade levels, have not yet fully utilized instructional media evenly. Traditional one-way teaching methods are still commonly used, and some students struggle to grasp the basic concepts. This study aims to improve students' conceptual understanding in the Informatics subject by utilizing instructional videos developed with Adobe Express as a learning medium. The research employed a quantitative method using a quasi-experimental approach, specifically the Pretest-Posttest Control Group Design, conducted at SMPN 2 Sindangagung. The study population consisted of 56 students from classes VII A and VII B. Data collection was carried out through field observations and interviews to gain insights into the learning environment and student conditions, as well as through questionnaires to obtain measurable research results. The collected data were analyzed using normality tests, homogeneity tests, and hypothesis testing. The expected outcome of this research is an improvement in students' conceptual understanding of Informatics, which can contribute positively to both teachers and schools.